Desenvolvimento Municipal das Microrregiões do Estado do Tocantins: uma análise a partir do Índice Firjan de Desenvolvimento Municipal - Ana Lucia Medeiros (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
This article aims to analyze the municipal development of the micro regions in the State of Tocantins, taking as temporal mark the years 2000 and 2010, starting from the Firjan Municipal Development Index – FMDI. The theoretical basis takes into account the thought of Amartya Sen, who presents a new look at economic development, understanding it as a process of expanding the real freedoms that people enjoy in order to fulfill what they want. This analysis aims at analyzing data on GDP per capita, public expenditure on health and education functions and the Firjan index of municipal development, and, based on the tabulation of data, it was possible to map the municipal development of the micro-regions of the State of Tocantins. The main finding of the study shows that over the ten years, there was growth in the development indicator in the municipalities of Tocantins, where the health and education dimensions were those that had the largest participation in the FMDI.